2007
DOI: 10.1086/512536
|View full text |Cite
|
Sign up to set email alerts
|

Is There a High‐Energy Particle Population in the Quiet Solar Corona?

Abstract: A study of spectra emitted by the quiet solar corona indicates that the majority of line intensities originating in lowlying levels are consistent with isothermal plasma of $1:3 ; 10 6 K. Nevertheless, a number of line intensities and, in particular, those belonging to ions that are typical of higher temperatures are brighter than expected. We show in this paper that the excess brightness of the hotter lines may be satisfactorily accounted for by a two-Maxwellian electron distribution function. We have calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 40 publications
0
18
0
1
Order By: Relevance
“…Ralchenko et al (2007) found that quiet Sun spectral lines were compatible with a two Maxwellian temperature distribution, provided that no more than 5 %, 3 %, and 1 % belonged to a second Maxwellian distribution with peak energy of 300-400, 500, and 1000 eV.…”
Section: Discussionmentioning
confidence: 97%
“…Ralchenko et al (2007) found that quiet Sun spectral lines were compatible with a two Maxwellian temperature distribution, provided that no more than 5 %, 3 %, and 1 % belonged to a second Maxwellian distribution with peak energy of 300-400, 500, and 1000 eV.…”
Section: Discussionmentioning
confidence: 97%
“…Instead, the spectra were consistent with multi-thermal plasma where the temperature of the second Maxwellian is at most log(T [K]) = 6.5 (Feldman, Landi, and Doschek, 2007, see Table 4 therein). Ralchenko, Feldman, and Doschek (2007) investigated the quiet Sun UV spectra of Si viii-Si xii, Ar xi-Ar xiii and Ca xiii-Ca xv ions observed by SUMER. These authors showed that these spectra are consistent with a bi-Maxwellian distribution, where the hot-temperature Maxwellian contains only a few per cent of particles.…”
Section: Diagnostics From Coronal Linesmentioning
confidence: 99%
“…By using the revised rate coefficient in Equation (2), the intensities of the lines used in the present work were calculated by representing the NTHE electrons with a second Maxwellian distribution with temperature T 2 , whose number of electrons is a fraction N of the total number of electrons in the plasma (0 N < 1). Using the work of Ralchenko et al (2007) as a guideline, we adopted a grid of values for both N and T 2 in order to explore these two parameters: N = 0, 0.01, 0.05, 0.1, 0.2 and log T 2 = 6.0, 6.3, 6.6, 6.9, 7.2, 7.5, and 7.8 (T in K). Figure 8 are shown for a temperature log T 2 = 6.9.…”
Section: Non-thermal Electronsmentioning
confidence: 99%